1987
DOI: 10.2135/cropsci1987.0011183x002700060025x
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Metabolism in the Primary Culm of Sweet Sorghum During Development1

Abstract: Sweet sorghum (Sorghum bicolor (L.) Moench] accumulates large amounts of sugar in culm parenchyma after anthesis, but the biochemical basis of this accumulation is not understood. This study was to identify the enzymes responsible for the pattern of sucrose accumulation in sweet sorghum. Sugars and four enzymes of sucrose metabolism were extracted from whole primary culms and individual internodes of primary culms of ‘Rio’ sweet sorghum at intervals during reproductive development. In whole culms, sucrose conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
1
6

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 0 publications
7
47
1
6
Order By: Relevance
“…Sugar accumulation in the stem of grain and sweet sorghum cultivars Previous reports have indicated that in sorghum stems, sugars start to accumulate at flowering stage [16,25]. We compared the accumulation of sugars in the stem between six sweet sorghum lines (Dale, Della, M81-E, Rio, Top76-6, and Simon) and one line from grain sorghum (BTx623).…”
Section: Resultsmentioning
confidence: 99%
“…Sugar accumulation in the stem of grain and sweet sorghum cultivars Previous reports have indicated that in sorghum stems, sugars start to accumulate at flowering stage [16,25]. We compared the accumulation of sugars in the stem between six sweet sorghum lines (Dale, Della, M81-E, Rio, Top76-6, and Simon) and one line from grain sorghum (BTx623).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the enzyme activities involving sucrose metabolism maintain a certain activity at low temperatures (Guy et al, 1992). of different varieties of sweet sorghum straw was not exactly the same (Lingle, 1987). The results of this study showed that the water content, total sugar content and main sugar content such as sucrose, glucose and fructose in the stalks of four sweet sorghum cultivars plants slightly decreased during the winter time from the early November 2016 to the March 2017, the lowest temperature was below 0°C, and the average temperature was near 0°C.…”
Section: Discussionmentioning
confidence: 93%
“…Esto explica la alta concentración de azúcares en las líneas A, B de sorgo y por tanto coincide con Lingle (1987) el cual reporta, que la madurez fisiológica del grano es la etapa óptima para la cosecha.…”
Section: Resultados Y Discusión Líneas Isogénicas a B De Sorgounclassified